Laryngeal Squamous Intraepithelial Lesions: An Updated Review on Etiology, Classification, Molecular Changes, and Treatment. (March 2016) - Gale, Nina; Gnepp, Douglas R.; Poljak, Mario; Strojan, Primož; Cardesa, Antonio; Helliwell, Tim; Šifrer, Robert; Volavšek, Metka; Sandison, Ann; Zidar, Nina
Abstract : Laryngeal carcinogenesis is a multistep process, characterized by an accumulation of genetic changes associated with architectural and cytologic alterations, ranging from squamous hyperplasia to carcinoma in situ and encompassed by the terminology of squamous intraepithelial lesions (SILs). The etiology, classification, genetic changes, and malignant progression of these lesions are reviewed. Tobacco remains the principal etiological factor with gastroesophageal reflux disease recently considered as a possible factor. In contrast, there is little evidence that microbiological agents, especially human papillomavirus infection, are frequently involved in laryngeal carcinogenesis and probably <10% of SILs are driven by biologically active human papillomavirus infection. Light microscopy, despite a degree of subjectivity, remains the mainstay of accurate diagnosis, prognosis, and guidance for a patient's treatment. The currently used classifications, the dysplasia system, squamous intraepithelial neoplasia, and the Ljubljana classification, reflect different standpoints on this important topic. The modified Ljubljana classification, with good interobserver agreement, could be considered as a proposal for a unified classification of laryngeal SILs. This review also briefly discusses recently discovered genetic changes, such as CDKN2A and CTNNB1 genes, and chromosome instability of chromosomes 1 and 7; however, none of these can at present improve histologic diagnosis. Malignant progression of precursor lesions varies from 2% to 74%, according to different studies. Cold-steel microinstruments, CO2 laser, and radiotherapy are used to treat the different grades of precursor lesions. There is as yet no worldwide agreement on the treatment of high-grade lesions and carcinoma in situ.